Effects of graded doses of sildenafil citrate on liver microanatomy in male albino rats - Sameena Bashir; Ghulam Mohammad Bhat; Shabir Ahmad Khanday; Lateef Ahmad Wani (Wolters Kluwer Medknow Publications, 2023)
Background: Sildenafil citrate (SC) is a vasoerectile drug used to treat impotence caused by erectile dysfunction by inhibiting phosphodiesterase type 5 enzyme. The drug is widely used and may have adverse effects on the liver as it is metabolized mainly in the liver. Therefore, the present research aimed to study the effect of graded doses of SC on the histological structure of the liver in albino rats. Methodology: The present prospective interventional experimental study was conducted on 30 albino rats. The rats were given SC in different doses and for different periods. Rats were sacrificed, and the liver was extracted and processed for histopathological examination. The slides were stained with hematoxylin and eosin and observed under a compound light microscope. Results: SC administrated in graded doses in male albino rats caused central venous congestion, sinusoidal dilatation, and fatty infiltration in the liver. These changes were more pronounced in rats that received the drug in higher doses and for a longer duration. The effects of SC on the rat liver microanatomy were dose and time dependent. Conclusion: SC is relatively safe in low doses, but at higher doses and longer duration, there can be adverse effects on the liver.